Evaluation of growth, physiological and biochemical traits of grafted neem (Azadirachta indicaA . juss) progenies in Tamil Nadu - Krishnan, P. Ratha; Paramathma, M. (Indian Journal of Agroforestry, 2020)
A study on preliminary evaluation of growth, physical and physiological traits of 21 CPT progenies (grafts) was conducted at Forest College and Research Institute, Mettupalayam, Tamil Nadu. The analysis of variance for different characters under study was found to be highly significant. At 6 MAP the clone FCRI - II recorded superior height, basal diameter, number of leaves, chlorophyll a, chlorophyll b, total chlorophyll, net photosynthetic rate and transpiration rate which was followed by Bannari II, Madurai and Ramanathapuram. Among the five biometrics observed, volume index registered higher PV, GV, PCV, GCV, heritability and genetic advance as percentage of mean, whereas the lower heritability and genetic advance as percentage of mean displayed by number of leaves. In case of biochemical and physiological traits highest PCV and GCV recorded for chlorophyll b and highest heritability was recorded for the trait IAA oxidase. The lower heritability was recorded for specific leaf area followed by stomatal conductance. Significant and positive phenotypic correlation of volume index was exhibited with plant height followed by basal diameter and number of leaves, whereas it had non-significant positive correlation with total phenol and IAA oxidase. Among the inter genotypic correlation, the higher value was recorded between chlorophyll b and chlorophyll a. Among the seventeen traits observed, ten traits expressed significant positive effect on volume index. The highest positive direct effect on volume index was exerted by basal diameter followed by specific leaf area. The highest negative direct effect on volume index was observed by total leaf area followed by soluble protein.